Human Resource Development In The Public Sector As A Catalyst For Regional Economic Development - Ani Nuraini; Darwati Susilastuti (PT. ALHAFI BERKAH INDONESIA, 2025)
This study explores the role of human resource (HR) development in the public sector as a catalyst in driving regional economic growth. A qualitative approach was used with a library research method and in-depth interviews with eight key informants from local government institutions, academics, and economic development practitioners. The study results indicate that planned, competency-based, and public service-oriented HR development can improve bureaucratic performance, accelerate decision-making, and encourage efficient governance. It has a direct impact on improving the investment climate and regional economic productivity. The study found that inter-sectoral collaboration and strengthening institutional capacity are significant factors in the success of the HR development agenda in the public sector. This study recommends improving the quality of training, performance-based evaluation, and utilizing digital technology as a strategy for sustainable HR development.